Dauru Mūsa Syāhīn Lāsyīn fī Al-Tashaddi li Al-Tatharruf Al-Fikri fī Fahmi Al-Hadīts - Zul Ikromi; Johar Arifin; Muhammad Reza Fadil (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This research discusses the role of Musa Shaheen in counteracting extreme thought through his writings relating to the discussion and thoughts of the Prophet's Sunnah. This research answers two important questions; how was Musa Shaheen Lashin's dedication to the Sunnah of the Prophet? And what is his role in dealing with extreme thought of understanding the Sunnah? This study concludes that Musa Shaheen Lashin took his time to serve the Sunnah of the Prophet and his knowledge. His idea of the whole Sunnah is that the tasyrī' is different from the opinion of Sheikh Mahmoud Shaltout, Rashid Rida, and Waliyullah Al-Dahlawi who view the division of Sunnah into tasyrī' and non-tasyrī'. Musa Shaheen wants to understand the Sunnah with the correct understanding without any division. Because, the division is a cause of misunderstanding or differences in viewpoints towards understanding the sunnah. Shaheen offers two important methods for understanding the Prophet's Sunnah properly. First, understanding the hadith through its context and meaning after paying attention to the text. Second, consider the conditions and circumstances, asbab al-wurud, objectives, and variables. Because these things are part of the law and even constitute the basic foundation and conditions. This theory aims to counteract the extreme thoughts that have emerged in several Islamic countries. Hadith experts must also be aware of the importance of historical, social, anthropological and asbab al-wurud contexts, so as not to place the text in a wrong, extreme, or careless form. Shaheen has dedicated his life to the Prophet's Sunnah by promoting moderate Islam as a religion of peace, safety and tolerance.